Pemahaman Problem Based Learning Mahasiswa Melalui Diskusi Interaktif Pada Program Kuliah Tamu - Janah, Roikhatul; Tsamrotul Ihtiari, Dhiya Ayu (Dawuh Guru: Jurnal Pendidikan MI/SD, 2025)
The guest lecture program in collage serves to update knowledge and improve student skills about the knowledge being studied. The organization of public lectures can be carried out through various teaching methods, one of which is the interactive discussion method. The interactive discussion method in this study was used to teach students about the problem-based learning model. The purpose of this research is to find out about students' understanding of problem-based learning through interactive discussions. The research method used in this research is quantitative with the type of pre-experiment using the one group pretest-postest design. The results showed that the interactive discussion method in online guest lectures significantly improved students' understanding of Problem Based Learning (PBL), with an average N-Gain value of 0.73 (high category) and significant paired t-test results (t = -2.291; p = 0.031 < 0.05), indicating that this approach is effective in creating a collaborative learning environment that encourages knowledge construction through three key stages (preparation, implementation, and closing).